Neuro–immune–tumor axis in gliomas: a review of mechanisms, models, and translational opportunities - Xu, Lu; Chen, Shuangyu; Fu, Yixin; Zhou, Tingting; Yu, Jianghao; Li, Jiayang; Chen, Wei (Frontiers in Immunology, 2025)
Neuroimmuno-oncology is an emerging interdisciplinary field that explores the complex interactions among the nervous system, the immune system, and tumor cells within the tumor microenvironment (TME). Recent studies have underscored the critical role of neurons in gliomas, where synaptic signaling and the release of neurotrophic factors contribute not only to tumor progression but also to mechanisms of immune evasion. Neurotransmitters such as glutamate and gamma-aminobutyric acid (GABA), along with neuron-derived factors including brain-derived neurotrophic factor (BDNF) and neuroligin-3 (NLGN3), have been shown to modulate immune cell function and promote the formation of an immunosuppressive TME. In particular, neuronal electrical activity mediated through α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) signaling facilitates immune escape in glioma cells, leading to the development of an “immune-excluded” phenotype that compromises the efficacy of immunotherapy. Therapeutic strategies that combine AMPAR antagonists with immune checkpoint inhibitors—alongside neuromodulatory techniques such as repetitive transcranial magnetic stimulation (rTMS) or deep brain stimulation (DBS)—hold potential to reprogram the neuro–immune–tumor axis, remodel the immune landscape, and improve immunotherapy responses in central nervous system malignancies. Advancing our understanding of how neuronal activity regulates the glioma immune microenvironment may open new avenues for precision-targeted therapeutic approaches in neuro-oncology.